Pandangan Majelis Ulama Indonesia KotaLubuklinggau Tentang Kriminalisasi Terhadap Ulama Dalam Perspektif Yuridis Sosiologis - Priyadi; Alexander, Ongky; Anwar, Syaiful; Edi Nepri, Johan (Hutanasyah : Jurnal Hukum Tata Negara, 2026)
The criminalization of ulama has become an issue of serious concern from the perspectives of constitutional law and the socio-religious life of society. This phenomenon is not only related to law enforcement but also concerns the protection of citizens’ constitutional rights, freedom of religion, and social stability. In practice, legal actions against ulama often raise debates regarding the boundary between objective law enforcement and the potential abuse of authority that may lead to criminalization. This study aims to analyze the views of the Indonesian Ulema Council (Majelis Ulama Indonesia/MUI) of Lubuklinggau City regarding the criminalization of ulama from a juridical-sociological perspective. The research method employed is empirical legal research with a juridical-sociological approach. Data were collected through interviews, observations, and documentation studies of relevant laws and regulations, particularly Law Number 16 of 2017 concerning Community Organizations. The findings indicate that the MUI of Lubuklinggau City emphasizes the importance of fair, transparent, and non-discriminatory law enforcement for all citizens, including ulama. Furthermore, from a sociological perspective, the criminalization of ulama has the potential to create social unrest, reduce public trust in religious leaders, and disrupt social harmony in community and state life.